A Overview Of Caregiver Support In Long-Term Care In Stroke Patients In The Work Area Of The Sukodono Health Center - Titi Tuffahati; Dony Sulystiono; Siti Maimuna; Alfi Maziyah (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2025)
Stroke is the leading cause of death and disability globally, so the role of caregivers is important in meeting the long-term care needs of stroke patients. This study aims to describe the support received by caregivers with stroke. This study uses a qualitative descriptive design with a total sampling approach with a total of 41 caregiver respondents. The instruments used were questionnaires that included emotional support, reward support, instrumental support, and informational support, collected through live interviews. The data were analyzed univariately to describe the percentage of support. The results showed that the majority of caregivers received good instrumental support (87.80%), followed by information support (78.05%), emotional support (75.61%), and reward support (63.41%). These findings indicate that, although instrumental support and information are quite high, efforts are still needed to improve emotional support and appreciation for caregivers with stroke for optimal long-term care. This study emphasizes the importance of interventions that focus on holistic support for caregivers.